Effect of cycling and thermal control on the storage and dynamics of a 40-L monolithic adsorbed natural gas tank. (15th May 2019) - Prosniewski, Matthew; Rash, Tyler; Romanos, Jimmy; Gillespie, Andrew; Stalla, David; Knight, Ernest; Smith, Adam; Pfeifer, Peter
Highlights: Non-methane components can cause ANG systems to have a 16% drop in storage. Thermal control decreases the volumetric storage due to cycling by 9%. ANG systems after extended cycling discharge 90–95% of the original discharged mass. Storage loss in ANG systems can decrease the thermal shifts in the tank up to 14.6 °C. With extended cycling, larger hydrocarbons displace previously retained ethane. Abstract: Adsorbed natural gas systems have been proposed as a cost-effective storage alternative to compressed and liquefied natural gas. This has led many groups to search and design sorbent materials with large methane storage capacities since natural gas is approximately 90% methane. The other 10% of natural gas contains larger hydrocarbons which can decrease the useable storage capacity of adsorbent systems. In this work, the effect of large hydrocarbons on the storage and dynamics of a 40-L adsorbed natural gas system, containing 20.5 kg of monolithic carbon adsorbent, produced by the University of Missouri, is reported. It was found that over the course of 20 cycles, due to the retention of 1.9 kg of non-methane components by the monoliths, the useable volumetric storage dropped 16%, and the amount of gas delivered dropped 10%. A second cycling experiment found that by using thermal control while the system discharged, the mass retention decreased to 0.91 kg, and the useable volumetric storage and delivered mass only dropped 7% and 5%, respectively. The effects of the mass retention, storage loss, and thermal control on the system's charge and discharge dynamics were then analyzed to provide a complete picture of the long-term effects of cycling large scale adsorbed natural gas systems with and without active thermal control.